A Linguistics Landscape Study on Prawirotaman Street Yogyakarta - Setyawan, Agustinus Hary; Rahmawan, Andi Dian; Yuniarto, Hendy (Linguistic, English Education and Art (LEEA) Journal, 2024)
This study explores the linguistic landscape of Prawirotaman Street in Yogyakarta, focusing on three research questions: the languages and language strategies used in public signs, public attitudes towards these languages, and the public's perception of their usage. The intersection of global communication needs and local heritage preservation is examined through a qualitative methodology involving photography and interviews. Using Cenoz & Gorter’s classification system, 51 units of analysis were identified and categorized according to Thongtong Tiwahporn's classification classification of signs. Additionally, interviews with shop owners, employees, and tourists were conducted to understand the motivations behind linguistic strategies and their attitudes towards English, Javanese, Indonesian, and other languages. The study found that Code Mixing was the most prevalent language strategy, used in 35% of the signs, followed by Hybrid Syntactic Structures and Abbreviations. Quantitative data revealed that 51.85% of the signs were monolingual, while 48.14% were bilingual, with English being the most frequently used language. The public's perception of language use varied, with 46% expressing positive attitudes and 27% very positive. The results highlight the delicate balance between meeting international tourism demands and preserving local linguistic heritage. This comprehensive approach, combining qualitative insights and quantitative data, provides a nuanced understanding of the linguistic landscape in Prawirotaman Street, contributing valuable insights into language use in urban tourism contexts. Keywords Linguistic Landscape, Public Sign, Prawirotaman, Public Attitude, Public Perception